Effect of sticky rice on the strength and permeability of bio-cemented sand - Zhang, Qiyong (2025)
Microbially induced carbonate precipitation (MICP) is an eco-friendly soil improvement technique. However, this method still has some drawbacks, such as low conversion efficiency of CaCO3 crystallization, insufficient strength for certain applications, and requiring multiple treatments. Previous studies have reported that sticky rice can regulate CaCO3 crystals (i.e., chemical CaCO3) in the sticky rice-lime mortar, showing potential for improving the bio-cementation. Therefore, this study explored the possibility of using sticky rice to enhance the biocementation effect. Tests were carried out to assess the strength and permeability of bio-cemented sand with the inclusion of sticky rice. The results indicated that sticky rice may regulate the type and size of bio-CaCO3 crystals, and the use of an appropriate amount of sticky rice as additive could increase the strength of sand columns by regulating CaCO3 crystallization. Polyhedral calcites may be more favourable for the increasing strength than some vaterites with a hollow spherical structure. The combination of MICP and sticky rice can significantly decrease the coefficient of permeability to a value that was much lower than that by using sticky rice and MICP alone. Bio-CaCO3 immobilized the sticky rice on one end on sand particles, and the reticulated structure of sticky rice divided large pores into small pores, which may be the important cause of the decrease in permeability coefficient. Finally, this study proposed that the MICP with the sticky rice as an additive may enhance the MICP effect and prevent the surface erosion of coarse-grained sand slopes.